Composting of laying hen manure with the addition of a yeast probiotic - Ruiz-Barrera, Oscar (2018)
This study assessed the effect of inclusion of a yeast probiotic on the counts of lactobacilli, total aerobes (TA), total coliforms (TC), E. coli and Salmonella in the composting of laying hen manure. The yeast probiotic concentration (0, 7.5 and 15% wet basis) in the composting effect was defined as factor A and the fermentation time (FT) (0, 7 and 23 days) was defined as factor B. A completely randomised design with a factorial arrangement of 3 3 and four replicates was used. An interaction was found in Salmonella and pH (p<.0001). The lowest (p<.05) Salmonella counts were obtained at day 7 in the treatments with 7.5% and 15%, respect to the control. The lowest values (p<.05) for pH were obtained at day 23 in the treatments containing 0 and 15%. Lactobacilli, E. coli, TC, whereas TA counts were affected only by fermentation time (p<.05). In all treatments, lactobacilli increased (p<.05) by day 7. E. coli and TC counts decreased (p<.05) across the fermentation time and TA remained constant for the first seven days. (p<.05). Anaerobic fermentation of poultry litter over 23 days is sufficient to lower the pH and eliminate pathogenic microorganisms.